Entre linhas de código e gênero: ciência de dados e experiências vividas na análise da discriminação de gênero na TI em Sorocaba - Mercado, Cristiane Palomar (Universidade Federal de São Carlos, 2026)
Despite the progress women have made in recent decades in terms of participation in the labor market and other spheres of public life, recent studies have revealed growing wage disparities affecting women. Considering the importance of the Information Technology (IT) sector to the Brazilian and global economy, it is essential to discuss wage differences and their impacts, especially on women's professional and personal lives. Therefore, the objective of this study is to analyze the wage disparities faced by women working in the Information Technology field in the city of Sorocaba, identifying and investigating the causes of these differences. The research sought to understand how socioeconomic, cultural, and organizational factors contribute to gender wage inequality in this sector. The study adopted a quantitative-qualitative approach. Initially, an analysis of data from the Annual Social Information Report (RAIS), from 2018 to 2022, for workers in the city of Sorocaba-SP, was carried out, followed by the application of the Oaxaca-Blinder decomposition method using the Python data science programming language. Subsequently, semi-structured interviews were conducted with IT professionals of both genders to investigate their perceptions and experiences of gender discrimination in the workplace. Finally, the research identified wage differences between men and women in the IT sector in Sorocaba, showing a significant increase in disparities: from 9.51% in 2018 to 19.45% in 2022. On average, 95% of this difference was attributed to discrimination. The interviews complemented these findings by offering a deeper understanding of working conditions and the factors that perpetuate wage inequality, revealing a scenario of discrimination, but also highlighting the importance of equity policies and initiatives that promote fairer environments.
Between lines of code and gender: data science and lived experiences in the analysis of gender discrimination in the IT sector in Sorocaba
Keywords: Tecnologia da Informação; Disparidade salarial; Information Technology; Discriminação de gênero; Data science; Gender discrimination; Wage inequality; CIENCIAS SOCIAIS APLICADAS; CIENCIAS SOCIAIS APLICADAS::ECONOMIA::METODOS QUANTITATIVOS EM ECONOMIA; 5. Igualdade de Gênero